Analisis Hubungan Kemandirian Belajar Dan Sikap Kreatif Siswa Terhadap Hasil Belajar Dalam Pembelajaran Kimia Kelas X Di SMA Negeri 6 Palu - Alifta Alifta; Tri Santoso; Dewi Satria Ahmar; Magfirah Magfirah (Universitas Tadulako, 2022)
This study aims to describe the description of learning independence, students' creative attitudes, and the relationship between learning independence and students' creative attitudes towards learning outcomes in class X chemistry learning at SMA Negeri 6 Palu. This research was conducted from April to June 2021. The research method used was descriptive research. The sampling technique is purposive sampling. The population in this study were all students of class X with a total of 90 students, the samples used were students of class X IPA 2 SMA Negeri 6 Palu in the academic year 2020/2021 as many as 30 students. The research instrument used in this study was a learning independence questionnaire and a creative attitude questionnaire compiled using a Likert scale, and using MID learning outcomes in semester 2 of chemistry class X IPA 2. Based on the results of the study, there were 3 categories of descriptions of independent learning and creative attitudes students are high, medium and low. The results of the calculation of the correlation coefficient between learning independence and student learning outcomes are low (rcount) 0.260. The relationship between creative attitudes towards student learning outcomes is moderate (rcount) 0.457 at the moderate level. Based on these data, it can be concluded that the creative attitude of students to support learning success is more positive than student learning independence. The results of this study are expected to be a source of information regarding the relationship between learning independence and students' creative attitudes towards learning outcomes